Synergistic effect of hybrid hydroxylated boron nitride and cellulose nanocrystals for enhancing the thermal, mechanical, and hydrophobic properties of composite film. Issue 1 (17th October 2022) - Sathwane, Manoj; Chhajed, Monika; Verma, Chhavi; Gaikwad, Kirtiraj K.; Maji, Pradip K.
Abstract: Hybrid composite films are largely preferred over neat films because of their superior thermal, mechanical, chemical, and hydrophobic properties. The hybrid composite film has a wide range of use, including space, defense, electronics, packaging, and engineering applications. Fabricating multifunctional hybrid composite films with biodegradable polymer and biodegradable filler such as cellulose nanocrystals has become popular in recent years as an alternative to conventional plastics. In this paper, hybrid hydroxylated boron nitride (BN) nanoparticles with CNC nano‐filer reinforced composite PVA films were fabricated. The obtained composite films were characterized for morphological, chemical, physical, thermal, and hydrophobic properties. The morphological analysis indicates that the hybrid nano‐filler was well dispersed in the poly(vinyl alcohol) (PVA) matrix. The reaction and hydrogen bond interactions between CNC and BN in composite films are confirmed by the Fourier transform infrared spectroscopy and x‐ray diffraction pattern. The contact angle method is used to confirm the enhancement of the hydrophobic property. The physical properties of the composite films and neat PVA film were analyzed by tensile test method using a universal testing machine. The thermal stability of the neat PVA film and the composite films were analyzed by the thermo‐gravimetric analysis method. The effect of hybridization of nanoparticles on the thermal, mechanical, and hydrophobic properties was studied. The hybrid composite film with enhanced properties allows it for multifunctional applications. Abstract :